EFEKTIVITAS MODEL JOYFUL LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA SMP DENGAN MEMPERHATIKAN DOMAIN SOAL - Yuniarti, Ratih Dwi; Situmorang, Risya Pramana; Krave, Agna Sulis (Science Education Programme Study, IKIP Veteran Semarang, 2018)
This study aims to determine the difference in understanding of the concept and effectiveness of the use of Joyful learning model by taking into account the Noting Domain Problem. This research is a quantitative research using quasi experimental design. The research sample is class VIII D using joyful learning model, and class VIII E using conventional model, which is chosen by purposive sampling. Technique that use for collecting understanding data is using written test, observation, and documentation. Hypothesis test using independent sample t test. The results showed that the use of Joyful learning model with attention to domain problems experienced show a significant increase and more effective than the conventional model of concept understanding. Joyful learning model effective approve of 0,04 < 0,05 (significant level 0.05) concluded that Joyful learning model is more effective than conventional learning model.